FORMING THE SINGLE PRODUCT MARKET OF EUROPEAN UNION COUNTRIES: EVOLUTION AND CONSEQUENCES OF LIBERALIZATION - Ю. Г. Козак; І. О. Уханова (Ринкова економіка: сучасна теорія і практика управління)
Single product market of European Union countries was created at the basis of Rome Treaty, according to which within the borders of EU the possibilities for free product trade have to be formed. Such step allows creating the powerful background for the future economics. But nevertheless, like any move towards integration, formation of single product market has been accompanied by a number of problems. This is a difficult sphere, which requires different countries’ politics harmonization at the different directions, covering the issues of physical and fiscal barriers, technical norms, taxation and other quantitative restrictions. That’s why, although it is assessed, that the European single product market has been formed already, there is a number of unsolved questions, which need developing additional regulatory documents and coherent policy between European Union countries.